Mirror therapy for phantom limb pain in moderate intellectual disability. A case report. (7th September 2021) - Folch, Annabel; Gallo, Daniel; Miró, Jordi; Salvador‐Carulla, Luis; Martínez‐Leal, Rafael
Abstract: Background: Phantom limb pain (PLP) is a common problem after limb amputation. There is mounting evidence supporting the use of mirror therapy (MT) in the treatment of individuals with PLP. However, there is no research studying the effects of MT on PLP in individuals with intellectual developmental disorders (IDD). The aim of this study was to increase our understanding of MT when used with adults with IDD and PLP through a case study approach. Methods: Here, we describe the use of MT with a 53‐year‐old female with moderate IDD and PLP, related to her left leg being amputated after ulcer complications. The study followed an A‐B‐A‐B design (baseline—treatment—withdrawal of treatment—re‐introduction of treatment), lasting 2 years, which included a long‐term follow‐up. Results: The data showed that the PLP sensation decreased after the MT treatment, with a raw change of 3.92 points and a 48% decrease in mean pain intensity ratings from pre‐ to post‐treatment. Conclusions: This is a unique case‐report on the use of MT with an individual with IDD suffering from PLP. The findings show that MT helped to significantly reduce the intensity of the PLP in this patient. Significance: This is a case‐report that illustrates how mirror therapy can be applied to people with intellectual developmental disorders and phantom limb pain. The results showed that phantom limb pain decreased after the mirror therapy, with a raw change of 3, 92 points and a percent change of 48%.